Development of Photovoltaic Cell Efficiency and Recycling - VÁCHA, Martin; LAPČÍK, Vladimír (GeoScience Engineering, 2024)
Photovoltaics are currently experiencing a huge boom in Europe. European policy is focusing on the deployment of renewables in the energy sector and the electrification of the European vehicle fleet. This article focuses on comparing the efficiency of different types of materials and technologies in the construction of PV panels and briefly summarises current technologies for recycling PV panels after the end of their productive life. One of the panels compared was part of a field measurement and its values are partly reported by the manufacturer, partly measured and partly calculated. The other values for the sample of materials used are obtained from scientific literature or annual reports of the manufacturers. The article shows that the original average values of 10% to 20% efficiency of PV panels are still shifting, and some materials and technologies now allow efficiencies of up to 38%. High hopes are especially placed on perovskite materials, GaAs cells, or combinations of these with other materials. Unfortunately, we have not made much progress in the recycling of photovoltaic panels and, with minor modifications, the methods already used for the first generation of photovoltaic panels are still used. These are mainly the mechanical method, the chemical method and combinations of these.